2018
DOI: 10.1038/s41467-018-02884-y
|View full text |Cite
|
Sign up to set email alerts
|

Microkinetics of alcohol reforming for H2 production from a FAIR density functional theory database

Abstract: The large-scale production of hydrogen from biomass under industrial conditions is fundamental for a sustainable future. Here we present a multiscale study of the available reforming technologies based on a density functional theory open database that allows the formulation of linear scaling relationships and microkinetics. The database fulfills the FAIR criteria: findability, accessibility, interoperability and reusability. Moreover, it contains more than 1000 transition states for the decomposition of C2 alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
58
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 51 publications
5
58
2
Order By: Relevance
“…As we have explained above, many functional groups are present in different parts of the molecule. In many cases, we have found that the barriers of several parallel paths are comparable, thus they might be active simultaneously . This means that a successful analysis of the reaction network requires the use of microkinetic models so that the molecular insight obtained for all elementary steps can be mapped to experimental data like reaction orders, activation barriers, activity of catalyst, and product selectivity .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…As we have explained above, many functional groups are present in different parts of the molecule. In many cases, we have found that the barriers of several parallel paths are comparable, thus they might be active simultaneously . This means that a successful analysis of the reaction network requires the use of microkinetic models so that the molecular insight obtained for all elementary steps can be mapped to experimental data like reaction orders, activation barriers, activity of catalyst, and product selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…This reduction is very convenient to optimize reaction conditions. However, this approach cannot be used to screen catalytic systems, as the potential catalysts might prefer different reaction paths, e. g ., the reforming of ethanol on Pd and Pt . Another approach is to consider flow reactors to be in quasi‐equilibrium.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations